2011
DOI: 10.1021/la200450x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biological Media on the Structure and Behavior of Ferrocene-Containing Cationic Lipid/DNA Complexes Used for DNA Delivery

Abstract: Biological media affect the physicochemical properties of cationic lipid-DNA complexes (lipoplexes) and can influence their ability to transfect cells. To develop new lipids for efficient DNA delivery, the influence of serum-containing media on the structures and properties of the resulting lipoplexes must be understood. To date, however, a clear and general picture of how serum-containing media influences the structures of lipoplexes has not been established. Some studies suggest that serum can disintegrate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 22 publications
4
29
0
Order By: Relevance
“…2). These results confirm those of our past studies, 5557, 60 indicating that serum proteins have a deleterious effect on transfection of cells with BFDMA.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…2). These results confirm those of our past studies, 5557, 60 indicating that serum proteins have a deleterious effect on transfection of cells with BFDMA.…”
Section: Resultssupporting
confidence: 92%
“…S9B†) suggests that addition of serum does not cause complete loss of the L α c nanostructure of the BFDMA RED lipoplex. This result appears consistent with these prior cryo-TEM results, 60 which indicated that some intact multilamellar, L α c nanostructures also appeared to survive addition of serum under certain conditions. The results shown in Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Several processing and formulation factors are expected to affect the efficiency with which these events can take place and subsequently, their biological activity and the colloidal characteristics of the resultant particles. Examples of such factors include (1) lipid composition [15,24] (2) charge ratio [31,32,44] (3) type and ratio of helper lipid [8,13,34] (4) type of the hydrophobic anchor of PEG-lipids in PEGylated lipoplexes [17] and (5) complexing medium [12,22].…”
Section: Introductionmentioning
confidence: 99%